The Evaluation of an Unfavourable Used of Humidifier Air Cooler - Supono, Ihsan; Ardiatna, Wuwus (Instrumentasi, 2019)
The humidifier cooler (or commonly known as air cooler) is a common device used by individuals to gain a more comfortable space and widely available in Indonesian market. Regarding either prices or power consumption, this device is an intermediate choice among household appliances with similar purpose, such as air fan and refrigerator-based air conditioner (AC). However due to the device working mechanism, there could be a possibility transfer of evaporated liquid from cold water flow to the output air flow that probably makes an increase of the relative humidity of the room space. This phenomenon raises a concern because the rise of the relative humidity during an attempt to reduce air temperature is undesirable due to the thermal comfort principle. Through simulations, it can be evaluated that room temperature could be kept at 26,4Â°C and 28,1Â°C for a normal and an unfavourable condition, respectively. However, there is an increase of room humidity by 38,1% which is significant enough to shift room condition toward an unhealthy state.